Obesity and Weight Loss: The Influence of Thyroid Hormone on Adipokines - Luvizotto, Renata de Azevedo Melo; Conde, Sandro José; Oliveira, Miriane de; Sibio, Maria Teresa De; Jr, Keize Nagamati; Nogueira, Célia Regina (IntechOpen, 2012)
None